2018
DOI: 10.2494/photopolymer.31.45
|View full text |Cite
|
Sign up to set email alerts
|

Printing of Lenticular Lens Patterns Using Defocused Projection Lithography

Abstract: A new optical lithography method for fabricating humpbacked pattern arrays was developed. The patterns were printed by adopting intentionally defocused projection exposure under the condition of very low numerical aperture of 0.089. As a resist, approximately 100-µm thick SU-8 (MicroChem) was used, and appropriate defocuses were 1400-2000 µm. When the exposure time and the defocus were changed, curvature radiuses of lens patterns were controllable in a wide range of 70-300 µm. The curvature radii became large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…And, on the way to develop a method for fabricating micro-flow path patterns with vertical side walls using a 100-µm thick negative resist of SU-8 (MicroChem) [1,2], it was found that semi-cylindrical patterns closely connected with neighbored ones were formed when line-and-space (L&S) patterns were projected under largely defocused conditions. In addition, the curvature radii of semi-cylindrical surfaces were controllable in a wide range [3]. The semi-cylindrical curves were very similar to the surface profiles of lenticular lenses used for switching two pictures alternately or making three dimensional photographs observable without any special glasses.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…And, on the way to develop a method for fabricating micro-flow path patterns with vertical side walls using a 100-µm thick negative resist of SU-8 (MicroChem) [1,2], it was found that semi-cylindrical patterns closely connected with neighbored ones were formed when line-and-space (L&S) patterns were projected under largely defocused conditions. In addition, the curvature radii of semi-cylindrical surfaces were controllable in a wide range [3]. The semi-cylindrical curves were very similar to the surface profiles of lenticular lenses used for switching two pictures alternately or making three dimensional photographs observable without any special glasses.…”
Section: Introductionmentioning
confidence: 62%
“…The quartz plates had a thickness of 240 µm and a size of 50 mm square, and the semi-cylindrical patterns were formed using a film reticle with 50µm L&S patterns. As a lithography tool, a handmade projection exposure system was used [1][2][3]. The exposure light source was an ultra-high pressure mercury lamp (Inflidge, UV-CURE120).…”
Section: Fabrication Of Lenticular Lens Patternsmentioning
confidence: 99%